Hazarat Noah (AS) - Karam , Ambia (Karachi , Lahore Children's publications)
He is one of the Ulul 'azm prophets. Noah's mission was to warn his people, who were plunged in idol worshipping. God charged Noah with the duty of preaching to his people, advising them to abandon idolatry and to worship only God, and to live good and pure lives.